Campylobacter coli infection causing second trimester intrauterine growth restriction (IUGR): a case report and review of the literature. (18th September 2015) - Kuperman‐Shani, Adi; Vaknin, Zvi; Mendlovic, Sonia; Zaidenstein, Ronit; Melcer, Yaakov; Maymon, Ron
Abstract: Campylobacter is a gram‐negative, microaerophilic, curved rod and a normal resident of the gastrointestinal flora and may be the cause of disease in animals. Transmission to humans occurs by ingestion of contaminated food or by direct contact with infected animals. In the past few decades, an increasing number of reports have implicated the presence of this organism in human abortions as well. An infectious mechanism due to primary placental inflammatory damage followed by secondary damage to the fetus following placental insufficiency and ischemia was suggested. The most common species of Campylobacter are Campylobacter jejuni and Campylobacter coli, which are classically associated with enteritis in humans. We present a rare case of mid‐gestation intrauterine growth restriction (IUGR) associated with maternal bacteremia caused by C. coli infection. Our literature review focuses on Campylobacter infections occurring in the second and third trimesters of pregnancy. In all cases, mild maternal symptoms consisting of fever and weakness were presented. However, associated adverse fetal outcome, including abortions, IUGR or preterm labor may occur more frequently than anticipated. Our report strengthens the importance of awareness to this finding and focuses the need to consume properly cooked meat during pregnancy. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Campylobacter is a gram‐negative, microaerophilic, curved rod and a normal resident of the gastrointestinal flora and may be the cause of disease in animals. Transmission to humans occurs by ingestion of contaminated food or by direct contact with infected animals. In the past few decades, an increasing number of reports have implicated the presence of this organism in human abortions as well. What does this study add? Mid‐gestation intrauterine growth restriction (IUGR) associated with maternal bacteremia can be caused by Campylobacter coli infection. Our report strengthens the importance of awareness to this finding and focuses the need to consume properly cooked meat during pregnancy.